Mobile technology dominates school children’s IT use in an advantaged school community and is associated with musculoskeletal and visual symptoms - Straker, Leon; Harris, C.; Joosten, J.; Howie, E. (Taylor & Francis, 2017)
© 2017 Informa UK Limited, trading as Taylor & Francis Group This paper describes the contemporary use of information technology devices by children in a socio-educationally advantaged school. A sample of 924 children (50% girls) from grades 5 to 12 (ages 10–19 years) completed an online survey in class. Total daily technology use was high and similar for girls (mean 219 (SD 148) mins/day) and boys (207 (142), p=.186). Tablet computer was the dominant device used in grades 5–9, with laptop computer the dominant device in grades 10–12. Patterns of exposure were influenced by gender, device, grade and purpose of use interactions. For example, girls used mobile phones more than boys for social purposes for grades 10 and 11, but not grade 12. Whilst children’s attitudes to technology use were positive, musculoskeletal and visual symptoms were commonly reported. Hours/day tablet and phone use was related to neck/shoulder discomfort (OR = 1.07; 1.13) and visual symptoms (OR = 1.10; 1.07). Practitioner Summary: Technology use by children appears to be quite different now to a decade ago. This paper describes contemporary school children’s use of various devices for various purposes. The survey of > 900 children found high technology use, dominated by new mobile technologies, and associations with musculoskeletal and visual symptoms.